2017
DOI: 10.1155/2017/3685261
|View full text |Cite
|
Sign up to set email alerts
|

Galactomannan in Bronchoalveolar Lavage Fluid for Diagnosis of Invasive Pulmonary Aspergillosis with Nonneutropenic Patients

Abstract: Background We evaluated the utility of galactomannan (GM) in bronchoalveolar lavage fluid (BALF) for the diagnosis of invasive pulmonary aspergillosis (IPA) in nonneutropenic patients. Methods A total of 183 patients were included in the final analysis. Bronchoscopies and the detection of GM in BALF were all performed on them. Results Ten cases of IPA were diagnosed. ROC data demonstrated that, for diagnosing IPA, an optimal cutoff value for GM in BALF of 0.76 yielded a sensitivity of 100.0% and a specificity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The presence of one or more cavities with fungal ball is almost definitive of CPA; however, fungal ball is seen only in about 40 to 60% of all cases (68% in the current study) (3). The Aspergillus precipitins have poor sensitivity (20 to 25%), while A. fumigatus-specific IgG has a sensitivity of 85 to 92% (98.4% in the current study) (3,9,11). Thus, the diagnosis of CPA relies primarily on the demonstration of A. fumigatus-specific IgG (9).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The presence of one or more cavities with fungal ball is almost definitive of CPA; however, fungal ball is seen only in about 40 to 60% of all cases (68% in the current study) (3). The Aspergillus precipitins have poor sensitivity (20 to 25%), while A. fumigatus-specific IgG has a sensitivity of 85 to 92% (98.4% in the current study) (3,9,11). Thus, the diagnosis of CPA relies primarily on the demonstration of A. fumigatus-specific IgG (9).…”
Section: Discussionmentioning
confidence: 61%
“…Most evidence on the utility of serum and bronchoalveolar lavage fluid (BALF)-GM estimation comes from subjects with invasive pulmonary aspergillosis (IPA) (1,(10)(11)(12). There are limited data from retrospective studies regarding the utility of serum or BALF-GM in diagnosing CPA (13)(14)(15).…”
mentioning
confidence: 99%
“…However, recent studies have found that the incidence of IPA is increasing year by year in nonneutropenic patients ( 8 ). The sample sizes of most studies of nonneutropenic IPA ( 9 , 10 ) are small. This article included more nonneutropenic IPA patients and increased the reliability of our conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with data from previous studies (21,22), there is a certain difference between the BALF GM value of patients with chronic airway inflammation and the BALF GM value of patients with various underlying diseases or neutropenia. It is believed that the GM test may need to be based on different underlying diseases or immunity, such as neutropenia and non-neutropenia (23,24), organ transplantation and non-organ transplantation (25,26), and hematological tumors (27,28), but setting different optimal thresholds may require more research to confirm. The best cutoff value of BALF GM in pulmonary Aspergillus patients with different risk factors should be set according to the results of BALF GM tests, further increasing the diagnostic efficacy of BALF GM for pulmonary aspergillosis cooccurring with other conditions.…”
Section: Discussionmentioning
confidence: 99%